Interface Engineering Between Multi‐Elemental Alloy Nanoparticles and a Carbon Support Toward Stable Catalysts. Issue 9 (11th January 2022) - Li, Tangyuan; Dong, Qi; Huang, Zhennan; Wu, Lianping; Yao, Yonggang; Gao, Jinlong; Wang, Xizheng; Zhang, Haochuan; Wang, Dunwei; Li, Teng; Shahbazian‐Yassar, Reza; Hu, Liangbing
Abstract: Multi‐elemental alloy (MEA) nanoparticles have recently received notable attention owing to their high activity and superior phase stability. Previous syntheses of MEA nanoparticles mainly used carbon as the support, owing to its high surface area, good electrical conductivity, and tunable defective sites. However, the interfacial stability issue, such as nanoparticle agglomeration, remains outstanding due to poor interfacial binding between MEA and carbon. Such a problem often causes performance decay when MEA nanoparticles are used as catalysts, hindering their practical applications. Herein, an interface engineering strategy is developed to synthesize MEA–oxide–carbon hierarchical catalysts, where the oxide on carbon helps disperse and stabilize the MEA nanoparticles toward superior thermal and electrochemical stability. Using several MEA compositions (PdRuRh, PtPdIrRuRh, and PdRuRhFeCoNi) and oxides (TiO2 and Cr2 O3 ) as model systems, it is shown that adding the oxide renders superior interfacial stability and therefore excellent catalytic performance. Excellent thermal stability is demonstrated under transmission electron microscopy with in situ heating up to 1023 K, as well as via long‐term cycling (>370 hours) of a Li–O2 battery as a harsh electrochemical condition to challenge the catalyst stability. This work offers a new route toward constructing efficient and stable catalysts for various applications. Abstract : An interfacial engineering approach is used to improve the stability (e.g., nanoparticle agglomeration) of multi‐elemental alloy (MEA) nanoparticles on a carbon substrate. MEA–oxide–carbon catalysts with a hierarchical structure are synthesized via a high‐temperature thermal‐shock method. The catalysts show excellent thermal and electrochemical stability, holding great potential for a range of catalytic reactions.